Should one invest in software development for internal use? An experience report from a small company (Research, Society and Development, 2024)
Companies need to use software solutions to solve their internal problems and to execute existing processes. This can be done using third-party solutions or by developing their own solutions. The second case can also be an opportunity to undertake something that is necessary nowadays. However, it is necessary to consider the challenges associated with this type of decision, especially for micro and small companies that have more limited resources. Considering this scenario, the objective of this article is to present an experience report of a small company that found itself faced with the need to implement a reporting functionality for a particular client. Since in this case it was not possible to use third-party solutions and there was a possibility of undertaking it, the company chose to develop its own solution. The short-term results were satisfactory, however, in the medium term it was realized that costs associated with the evolution and maintenance of the software were not considered as they should have been. The results highlight the needs that should be considered by companies, especially small ones, when faced with the need to develop software solutions.